Some simple results for the properties of polar fluids - Henderson, D. (Condensed Matter Physics, 2011)
The author's lecture notes concerning the correlation functions and the thermodynamics of a simple polar fluid are summarized. The emphasis is on the dipolar hard sphere fluid and the mean spherical approximation and on the relation of these results to the Clausius-Mossotti and Onsager formulae for the dielectric constant. Previous excerpts from these lecture notes, Condens. Matter Phys., 2009, 12, 127; ibid., 2010, 13, 13002, have contained results that were not widely known. It is hoped that this third, and likely final, excerpt will prove equally helpful by gathering several results together and making these more widely available and recording a few new results.